SIFAT ANATOMI DAN KUALITAS SERAT JENIS KAYU SANGAT KURANG DIKENAL: SUKU CAPPARIDACEAE, CAPRIFOLIACEAE, CHLORANTHACEAE DAN COMPOSITAE - Sri Rulliaty (Jurnal Penelitian Hasil Hutan, 2014)
From the total of 34,410 wood samples collection of Xylarium Bogorienses 1915, there are about 800 species (251 genera of 77 tribes) which their anatomical properties have not been studied adequately. These wood species were grouped into “The Least Known Wood Species”. This paper studies anatomical properties and fiber quality of five wood species of “The Least Known Wood Species”. The studied species include Crataeva sp., Crataeva membranifolia Miq.,(Capparidaceae), Viburnum sambucinum Bl. (Caprifoliaceae), Ascarina sp. (Chloranthaceae) and Olearia sp. (Compositae). Samples were extracted from Xylarium Bogoriense 1915 collection. The anatomical properties were examined through sectioned samples based on the IAWA list of wood identification and fiber dimensions were observed from macerated samples. Results show that anatomical properties of the studied species are distinctive for identification purposes, such as Ascarina sp. and Olearia sp. which characterized with wide ray structures. Aggregate rays were present in Crataeva membranifolia and Ascarina sp. The heartwood of Crataeva membranifolia are yellowish in colour and has straight grain which can be used for substitution of ramin wood. Fiber quality of all the studied species are classified into class quality I for pulp and paper except Olearia sp. wood species which falls into class quality II.